STRATEGI MANAJEMEN PENGELOLAAN WAKAF PRODUKTIF DI PESANTREN YAYASAN ARWANIYYAH KUDUS - M Bastomi Fahri; Irham Zaki (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
Basically, waqf only have a direct function. Islamic boarding school didn't yet toproductive the land of waqf. Yayasan Arwaniyyah is a foundation with boarding school basic who can utilizing waqf land productively. This study aims to describe the manajement of waqf productif in Yayasan Arwaniyyah Kudus. This study is using qualitative approach with study case strategy. Analitical techniqueis based on theoritical preposition, that followed the theoritical preposition which guide the case of study. Arwaniyyah Foundation when utilize the waqf productive do several things, which is performing management fungtions in the implemetation of waqf productive, creating jobs and social care, and creating economic independence boarding school. The result of this research show that Arwaniyyah Foundation utilize lands waqf to be productive to achieve economic independence boarding school. Management of waqf conducted by the foundation divided into three areas. Religion activities, Islamic education, and social and economic.  REFERENCESAl Qur’an. Departemen Agama Republik Indonesia. Syamil Qur’an The Miracle 15 in I. 2009. Bandung: PT Sygma Examedia Arkanleema.Al Hajjaj, Abu Al Husain Muslim bin. 2015. Shohih Muslim. Offline. Maktabah Syamilah.Abdullah, Andika Rahmad. Manajemen Wakaf Produktif: Studi Pengelolaan Donasi Wakaf Bagi Pemberdayaan Ekonomi Umat Pada Dompet Dhuafa Republika. Jurnal Ekonomi UIN Malang. Online. (http:///etheses.uin-malang.ac.id/2522/12/19510109_Ringkasan.pdf, diakses pada 9 November 2016. Fakultas Ekonomi Univeristas Islam Negeri Malang.Al Bajuri, Syeikh Ibrahim. Hasyiah Al Bajuri ‘ala Ibnu Qosim Al Ghuzzi. Jakarta: PT Karya Insani.Al Bujairomi, Sulaiman bin Muhammad. 2015. Bujairomi ‘alaa al Khatib. Offline. Maktabah Syamilah.Al Hasani, Muhammad Ar Rouf Qosimiy. 2007. At Tathwiir At Takhrijiy wa At Tasyri’i li An Nidzomi Al Waqfi : Numudzujil Iqtishodi At Tazommuniy. Jordan: Chasier du CREAD.Amirullah dan Haris budiyono, 2003. Pengantar Manajemen. Yogyakarta: Graha Ilmu.Antonio, Muhammad Syafi'i Bank Syari'ah dari Teori ke Praktek. Jakarta: Gema Insani Prss dan Tazkia Cendekia.As Shan'ani, Muhammad Ibnu Isma'il. Subulus Salam. Mesir : Mushtafa Bab al Halabiwa Awladuh.At Thanthawi, Muhammad Sayyid 2013. Tafsir Al Wasith lit Thanthawi. Online. Al Mausu’ah As Syamilah.Dahwan. 2008. Pengelolaan Benda Wakaf Produktif. Jurnal UIN Sunan Kalijaga. Online. (http://digilib.uin-suka.ac.id/8240/1/DAHWAN%20PENGELOLAAN%20BENDA%20WAKAF%20PRODUKTIF..pdf, diakses pada 7 November 2016. Fakultas Ekonomi Universitas Islam Sunan Kalijaga Yogyakarta.Departemen Agama. 2003. Fiqh Waqf. Jakarta: Direktorat Pemberdayaan Wakaf Direktorat Jendral Bimbingan Masyarakat Islam Departemen Agama RI.Departemen Agama. 2005. Pola Pengembangan Pondok Pesantren. Direktorat Pendidikan dan Pondok Pesantren Departemen Agama RI.Emzir. 2012. Metodologi Penelitian Kualitatif: Analisis Data.  Jakarta: PT. Raja Grafindo Persada.Jawad Mughniyah. 1996. Fiqih Lima Madzhab: Edisi Lengkap. Jakarta: PT. Lentera Basrita.Wadjijiy, Farid dan Mursyid. 2007. Wakaf dan Kesejahteraan Umat “Filantropi yang Hampir Terlupakan”. Yogyakarta: Pustaka PelajarMoleong, Lexy J. 2005. Metodologi Penelitian Kualitatif, rev. Ed. Bandung: PT. Remaja Rosdakarya.Mubarak, Jaih. 2008. Wakaf Produktif. Bandung: Simbiosa Reksatama.Noor, Mahpuddin, H. 2006. Potret Dunia Pesantren. Bandung: Humaniora.Qomar, Mujamil. 2008. Pesantren: Dari Transformasi Metodologi Menuju Demokrasi Institusi, Jakarta: Erlangga.Saadati, Nila. 2014. Pengelolaan Wakaf Tunai dalam Mekanisme Pemberdayaan Ekonomi Pesantren (Studi pada Pondok Pesantren At Tauhid Al-Islamy Magelang). Tesis. Yogyakarta: Program Pascasarjana Universitas Islam Negeri Sunan Kalijaga.Sugiyono. 2014. Memahami Penelitian Kualitatif. Bandung: Alfabeta.Yin, Robert K. 2008. Studi Kasus:Desain dan Metode. Jakarta: PT. Raja Grafindo Persada.